2004
DOI: 10.1080/08958370490443213
|View full text |Cite
|
Sign up to set email alerts
|

Daily Mortality and Air Pollution in Atlanta: Two Years of Data from ARIES

Abstract: Associations between daily mortality and air pollution were investigated in Fulton and DeKalb Counties, Georgia, for the 2-yr period beginning in August 1998, as part of the Aerosol Research and Inhalation Epidemiological Study (ARIES). Mortality data were obtained directly from county offices of vital records. Air quality data were obtained from a dedicated research site in central Atlanta; 15 separate air quality indicators (AQIs) were selected from the 70 particulate and gaseous air quality parameters archi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…This study updates the findings presented in Klemm and Mason 4 and Klemm et al 5 on the relationship between air quality measures and daily mortality. In so doing, it discusses the impact of approximately 7.5 years (7 years and 5 months) of additional data on the analytical results.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…This study updates the findings presented in Klemm and Mason 4 and Klemm et al 5 on the relationship between air quality measures and daily mortality. In so doing, it discusses the impact of approximately 7.5 years (7 years and 5 months) of additional data on the analytical results.…”
Section: Introductionsupporting
confidence: 84%
“…5,6 Previous studies have identified associations between ambient (outdoor) PM and adverse health outcomes using a 2-day average of fine particulates and daily mortality. 7,8 We continue that approach during this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In 1999, 24-hr integrated measurements of PM 2.5 mass, SO 4 ϭ , EC, and OC and gaseous O 3 , SO 2 , and NO 2 were made. In 2000, the same measurements plus PM 10 were made. These data have been used not only to examine associations of indicators related to COPD and MI with exposures but also residential infiltration rates, relations among microenvironmental indoor and outdoor pollutant concentrations, and spatial variability over the domain spanned by the residences.…”
Section: Resultsmentioning
confidence: 99%
“…For example, polar organic compounds such as quinones are reported to act as catalysts to directly produce reactive oxygen species (ROS), resulting in oxidative stress (Kumagai et al, 1997;Squadrito et al, 2001); polycyclic aromatic hydrocarbons (PAHs) can induce oxidative stress indirectly, through their biotransformation to generate redox active quinones (Penning et al, 1999). VOCs concentration levels in the ambient air have been linked to the incidence of chronic respiratory symptoms and the frequency of hospital admissions due to ischemic heart disease and myocardial infarctions (Gordon et al, 1998;Klemm et al, 2004;Tolbert et al, 2001). In a recent exposure study of freeway traffic emissions on the cardiovascular effects of rats, vapor-phase components, rather than PM, were associated with a decrease in heart rate variability (Elder et al, 2007).…”
Section: Introductionmentioning
confidence: 99%